USE OF IMPROVED POST- COVID-19 REHABILITATION PROGRAMS IN HOTEL ENTERPRISES OF LVIV REGION - Шидловская, Елена; Ищенко, Татьяна; Бойцова, Анастасия; Медведь, Ирина (SWorldJournal, 2022)
The COVID-19 pandemic is in its third year. It has already affected millions of people around the world who are either ill or dying from the spread of the disease, or have been unable to recover from its long-term effects for a long time. It is for the ca